Uniform asymptotics for the ruin probabilities in a bidimensional renewal risk model with strongly subexponential claims. Issue 5 (4th July 2019) - Cheng, Dongya; Yu, Changjun
ABSTRACT: This paper considers a bidimensional continuous-time renewal risk model of insurance business with different claim-number processes and strongly subexponential claims. For the finite-time ruin probability defined as the probability for the aggregate surplus process to break down the horizontal line at the level zero within a given time, an uniform asymptotic formula is established, which provides new insights into the solvency ability of the insurance company.